0353 Objectively Measured Sleep and Components of Metabolic Syndrome in Well-Functioning Older Adults. (27th May 2020) - Hossain, S; Alfini, A J; Wanigatunga, A A; Rojo-Wissar, D M; Schrack, J A; Simonsick, E M; Zipunnikov, V; Wanigatunga, S K; Spira, A P
Abstract: Introduction: Prior studies tying sleep to metabolic syndrome in older adults have mostly used self-report sleep measures. We investigated the association between actigraphic sleep parameters and metabolic syndrome components in well-functioning older adults. Methods: We studied 434 participants in the Baltimore Longitudinal Study of Aging (aged 71.1±12.8 years, 41.4% women) with 6.6±1.0 nights of wrist actigraphy and data on metabolic syndrome components: blood triglyceride (TG) level >150 mg/dL; high density lipoprotein (HDL) <50 mg/dL; and waist circumference (WC) >88.9 cm for women and >101.6 cm for men. Sleep parameters were the primary predictors and metabolic syndrome components the outcomes. Logistic regression was performed, and results are expressed as odds ratio (OR) with p-values. Results: After adjusting for age, sex, race and education, higher sleep efficiency (SEFF; per 10%) was associated with a lower odds of high WC (SEFF OR=0.60, p=0.01) and, compared to participants in the intermediate total sleep time tertile (5.5 to 6.8 h), those in the shortest tertile (<5.5 h) had a slightly lower odds of high WC (TST OR=0.98, p=0.02). In adjusted models, greater wake after sleep onset (WASO; per 30 min), greater average wake bout length (WBL; per min), and lower SEFF (per 10%) were associated with a greater odds of poor HDL level (<50 mg/dL) (WASO OR=1.37, p=0.05; WBL OR=1.49, p=0.007; SEFF OR=0.72, p=0.04). After further adjustment for BMI and depressive symptoms, only the association between longer WBL and poor HDL level remained significant (OR=1.48, p=0.01). There were no associations between sleep parameters and TG level. Conclusion: Among well-functioning older adults, greater WASO but lower TST and SE are associated with poorer metabolic syndrome components. Longitudinal research is needed to evaluate the temporal associations of objectively measured poor sleep and metabolic syndrome components and evaluate the roles of BMI and depressive symptoms in these associations. Support: The first author is supported by a Postdoctoral Fellowship by the Intramural Research Program (IRP) at the National Institute on Aging (NIA). This study was supported in part by National Institute on Aging (NIA) grant R01AG050507, the NIA Intramural Research Program (IRP), and Research and Development Contract HHSN-260-2004-00012C.